2008
DOI: 10.1021/pr700878t
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics Analysis of Rice Lesion Mimic Mutant (spl1) Reveals Tightly Localized Probenazole-Induced Protein (PBZ1) in Cells Undergoing Programmed Cell Death

Abstract: Numerous reports have predicted/hypothesized a role for probenazole-induced protein (PBZ1) as a molecular marker in rice self-defense mechanism. However, the precise function of PBZ1 remains unknown. In the present study, we examined PBZ1 as a putative cell death marker in rice. For this, we focused our attention on a rice lesion mimic mutant (LMM), spotted leaf 1 ( spl1), which has been used to study the programmed cell death (PCD) phenomenon during lesion development in leaf. Using two-dimensional gel electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 60 publications
0
58
0
2
Order By: Relevance
“…The SAGE tag for beta-glucanase gene was detected six times, the cases for peroxidase four times, and the putative peroxidase genes twice. In general, both beta-glucanases and peroxidases have been known as enzymes that mediate the defense system against abiotic stresses such as ozone, H 2 O 2 and ultraviolet radiation (Cheong et al, 2000;Dabir et al, 2007;Kim et al, 2008b;Thalmair et al, 1996). The tags for PR-10 ( Kim et al, 2003;McGee et al, 2001;Tanaka et al, 2003) were detected a total of three times, suggesting that the protein seems to make a significant contribution as a biotic stress defense system.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The SAGE tag for beta-glucanase gene was detected six times, the cases for peroxidase four times, and the putative peroxidase genes twice. In general, both beta-glucanases and peroxidases have been known as enzymes that mediate the defense system against abiotic stresses such as ozone, H 2 O 2 and ultraviolet radiation (Cheong et al, 2000;Dabir et al, 2007;Kim et al, 2008b;Thalmair et al, 1996). The tags for PR-10 ( Kim et al, 2003;McGee et al, 2001;Tanaka et al, 2003) were detected a total of three times, suggesting that the protein seems to make a significant contribution as a biotic stress defense system.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, it was reported that the JIOsPR10 protein which is one of the PR-10 family possesses RNase activity that is dependent on sensitive to DTT, suggesting the importance of the disulfide bonding between cysteine residues (Kim et al, 2008a). In addition, expression level using Western blot, immunohistochemical, and its promoter analysis of PBZ1 protein (PR-10 family) is tightly associated with plant cell death tissues, suggesting that PBZ1 could serve as a cell death marker protein as well as defense protein in rice (Kim et al, 2008b). Thus, they might play a role in self-defense mechanisms in plants against biotic and abiotic stresses.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, defense-related proteins were differentially expressed in the mutant (Tsunezuka et al 2005). Among the numerous proteins induced in a rice lesion mimic Average of signal intensity represents an average measurement of the abundance of each gene transcript during the experimental period mutant, spotted leaf1 (spl1), the PBZ1 protein was highly induced in leaves (Kim et al 2008). The in planta localization of the PBZ1 protein in rice leaves was found to be correlated with cell death caused by blast fungus infection (Kim et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The IPG strips were equilibrated as described previous research (Kim et al, 2011) and focused at 50 V for 8 h, 100 V for 1 h, 500 V for 1 h, 1000 V for 1 h, 2000 V for 1 h, 4000 V for 2 h, 8000 V for 5 h, 8000 V for 3 h, 20 V for 2 h, by IPGphore3 platform (GE healthcare, Waukesha, WI) and then 12% sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE) was carried out perpendicularly to the previous run. Separated proteins were stained with colloidal Coommassie brilliant blue G-250 (CBB) following the method of Kim et al (2008b). Stained gels were scanned using a transmissive scanner (PowerLook III, UMAX, Fort Worth, TX).…”
Section: Protein Preparation and 2-dge Analysismentioning
confidence: 99%
“…Protein spots were carefully cut off in CBB-stained gels, digested with trypsin, and peptides were extracted peptides according to the method of Kim et al (2008b). Extracted peptide mixture was re-dissolved in a solution composed of distilled water, acetonitrile, and trifluoroacetic acid (93:5:2; volume basis), bath-sonicated for 5 min, and centrifuged for 2 min at 14,000 rpm.…”
Section: In-gel Digestion and Matrix-assisted Laser Desorption/ Ionizmentioning
confidence: 99%